New Approach to Rare Pediatric Multicystic Mesenteric Lymphangioma; Would It Guide the Development of Targeted Therapy? - Heredea, Rodica; Cimpean, Anca M.; Cerbu, Simona; Popoiu, Calin M.; Jitariu, Adriana A.; Raica, Marius (Frontiers in Pediatrics, 2018)
In children, lymphangiomas are extremely rare pathologic entities that are characterized by unusual locations. The mesenteric localization is extremely rare in children, and the clinical signs usually mimic an acute abdominal syndrome. For most of the cases, their diagnosis is established by the radiologist, and the main therapeutic option is represented by surgery for lesion removal. We hereby describe the case of a 4 year old girl admitted to the pediatric emergency department for continuous abdominal pain, more intense in the orthostatic position, associated with abdominal distension, nausea and vomiting. These symptoms raised the clinical suspicion of acute abdominal syndrome. The patient had no previous clinically significant events. Radiologic examination suggested a mesenteric multicystic lymphangioma certified by surgical and histopathological evaluation. No specific targeted therapy is currently available; moreover, no specific criteria for recurrences have been stated. A new approach of infantile lymphangiomas following surgery, regarding the use of specific lymphatic markers panel including D2-40, Prox-1, VEGFR-3, PDGFs and Ki67 may improve the characterization of such lesions regarding their prognosis, recurrence rate and targeted therapy implementation especially for those with a more aggressive or recurrent behaviour.